Empiricism of Thomas Aquinas: The Question of the Object of Knowledge - Oniščik, Marija (Problemos, 2015)
The article deals with Thomas Aquinas’ theory of knowledge, emphasising the question of the object of knowledge. According to his ontological principles, Aquinas believes that the process of knowledge is of representational character and that what is represented is the form of a thing. Two faculties of knowing – sense and intellect – need two kinds of representation, which are phantasm – a sensible image of a thing made by imagination, and intelligible species – an intellectual image of a thing made by abstraction from a sensible image. This twofold representation, according to Aquinas, is necessary in order to guarantee the possibility of conceptualisation on which the meaningfulness of language depends.